In vivo analysis of the size- and time-dependent uptake of NaYF4:Yb, Er upconversion nanocrystals by pumpkin seedlings. Issue 1 (6th November 2014) - Nordmann, J.; Buczka, S.; Voss, B.; Haase, M.; Mummenhoff, K.
Abstract : We have investigated the kinetics of the uptake and the translocation of nanoparticles of different size in plants. Abstract : We have investigated the kinetics of the uptake and the translocation of nanoparticles in plants. Nearly monodisperse NaYF4 :Yb, Er nanocrystals were used, either spherical particles with a diameter of 14 nm or nanorods with a length of 41 nm and a diameter of 22 nm. After watering pumpkin seedlings ( Cucurbita maxima ) with aqueous colloidal solutions of the particles, intact nanocrystals in the plants were detected in vivo by exciting their upconversion luminescence with a near infrared laser diode (978 nm). The particle concentration in different plant parts was determined by X-ray fluorescence spectroscopy (XRF), making use of the high sensitivity of Yttrium in XRF measurements and its low natural abundance in plants. The results show a fast uptake and translocation of the nanoparticles in all plant organs within three hours. The smaller particles move in the plants faster than the larger ones.